Revolutionizing The Halal Food Industry: The Crucial Role of Green Halal Supply Chain in Pakistani Companies - A Compelling Theoretical Framework - Safiullah Junejo; M. Luthfi Hamidi; Saba Anwar (Muhammadiyah University Press, 2023)
The 13th Five Year Plan 2016-2020 (FYP) says that Pakistan wants to be a global hub for Halal food, and the country is on track to reach this goal by 2025. However, the progress needs to be supported by a complete ecosystem that lets the Halal supply chain close the compliance loop. So, calling for sustainable development to help strengthen the definition of